Virtual Clinical Listening Groups for Psychological Intervention With University Students in the COVID-19 Pandemic - Bloc, Lucas; de Araújo, Juliana Lima; Leite, João Marcos; Barreto, Sarah Rebeca; Carneiro, Karla; Melo, Anna Karynne; Boris, Georges; Moreira, Virginia (Frontiers in Psychiatry, 2022)
The pandemic has affected people's mental health and university students are considered one of the most vulnerable groups, encouraging the development of psychological interventions that can minimize the suffering and illness of this public. Among the possibilities of intervention, virtual clinical listening groups were created which, during the period of social isolation, had the purpose of opening up a listening space for university students suffering from emotional distress. The focus of the group meetings was how university students were experiencing the pandemic, as well as the consequences of this experience. In this article, we discuss virtual clinical listening groups as a form of psychological intervention in the mental health care of university students during the COVID-19 pandemic at a university in northeastern Brazil. This is a qualitative study that began with 274 university students and 5 psychologists who facilitated the listening groups. We used as instruments the registration forms, the participation records of the virtual clinical listening groups and the field diaries written by the facilitators after each meeting. We described in the results the collected data and, from the field diaries, the themes that emerged in the various meetings were listed and analyzed in dialogue with the literature. At the end of the psychological screening process, 117 students participated in the 17 organized groups, with an average of 8 university students per group. Among the main motivations for participating in virtual clinical listening groups, we highlight: the desire to share experiences, a search for control of anxiety, depression and stress, care for mental health, a willingness to promote listening to psychological support for themselves and for others, and self-knowledge. We discuss the nuances in the process of forming the listening groups and the characteristics of the participants, as well as a central element of the group process, which is the establishment of bonds and mutual help among the participants. Feeling vulnerable and the fear of contamination is an element of suffering and, above all, of stress experienced by university students. The group presented itself as an alternative of mutual care in the pandemic context.